Investigation of Memory Enhancing Activity of Combination Extracts of Bauhinia variegata and Madhuca longifolia Leaves against Colchicine: An Experimental Study and Biochemical Alterations in Mice - Khare, Pragati; Kishore, Kamal; Sharma, Dinesh Kumar; Khare, Noopur (Indian Journal of Pharmaceutical Education and Research, 2024)
Objectives: To investigate the role of combination of Madhuca longifolia (ML) and Bauhinia variegata (BV) ethanolic leaf extracts against oxidative damage in Swiss Albino mice and colchicine induced cognitive dysfunction; to estimate the neuroprotective impact using Madhuca longifolia and Bauhinia variegata combination by behavioral testing and to analyze the biochemical parameters. Materials and Methods: The experimental analysis was done for 28 days on a colchicine-induced model. Acute oral toxicity study was performed according to OECD 425 guidelines. Passive avoidance paradigm and Morris water maze were used for behavioral experiments and biochemical parameters like glutathione and nitric oxide were analyzed. 36 Swiss albino mice were grouped into six groups, each consisting of six mice. 1% w/v Carboxy Methyl Cellulose (CMC) was administered to the Group (G) I. The G II received ED(BV)+ED(ML) (400 mg/kg+200 mg/kg oral). G III was administered ED(BV)+ED(ML)+Col(400 mg/kg+200 mg/ kg+1 mg/kg, intracerebrovascular (i.c.v.)).The fourth group got ED(BV)+ED(ML)+Pir(400 mg/ kg+200mg/kg oral+200 mg/kg, intraperitoneal (i.p.)). Group V has been given LDBV+LDML (200 mg/kg +100 mg/kg oral) for 28 days and Colchicine 1 mg/kg, i.p., at 60 min after 28th day piracetam injection. Group VI received HDBV+HDML (400 mg/kg+200 mg/kg oral). Analysis of Variance (ANOVA) (one-way) was followed by Tukey’s test and then the results were analyzed. Results: Madhuca longifolia and Bauhinia variegata ethanolic leaf extracts indicated a decrease (p<0.001) in transfer latency of mice in Morris water maze. The transfer latency in passive avoidance model showed a significant increment (p<0.001). The Madhuca longifolia and Bauhinia variegata leaf extract combination showed an increment (p<0.001) in GSH levels and a decrease (p<0.001) in NO and total protein. Conclusion: The combination of Madhuca longifolia and Bauhinia variegata has neuroprotective effect against memory damage caused by colchicine.
Keywords: Madhuca longifolia; Neuroprotective; Alzheimer’s disease; Bauhinia variegata; Colchicine; Acetylcholinesterase; Cognition